Implications of District Court Decisions on the Stages of the 2024 Elections: Perspectives on the Indonesian Election System - Inagatha Setyarahma Pangastuti; Radian Salman; Mohammad Syaiful Aris; Luh Putu Yeyen Karista Putri (Pattimura Legal Journal)
Introduction: The stipulation of Decision Number 757/Pdt.G/2022/PN.Jkt.Pst raises many pros and cons, namely related to the decision to postpone the 2024 elections. Through the Decision, the Central Jakarta District Court decided and adjudicated the Unlawful Acts dispute filed by the Adil Makmur People's Party against the General Election Commission. The Central Jakarta District Court should not have the authority to adjudicate disputes filed by the Adil Makmur People's Party because it violates absolute competence.